Richards Curve Implementation For Prediction of Covid-19 Spread in Maluku Province - Ondi, Nanang; Rumlawang, Francis Yunito; Lesnussa, Yopi Andry (CAUCHY, 2022)
COVID-19 (Coronavirus Disease 2019) was first reported in Wuhan city, China at the end of December 2019 and spread to Indonesia specifically in Maluku Province at the end of March 2020. This study aims to predict the spread of COVID-19 cases in Maluku province as well as explore the phases of its spread using the Richards Curve which is an extension of the Logistic Curve. After estimating the parameters of the Richards Function with cumulative case data of COVID-19 in Maluku province from March 23 to November 4, 2020, the results of the spread of COVID-19 cases in Maluku province reached a turning point on October 22, 2020, and ended on May 25, 2023, with a total cumulative case of 9,451 cases